Pengaruh Literasi Keuangan, Kemudahan, Serta Kebermanfaatan dalam Keputusan Pengguna an E-Money pada Peningkatan Kinerja UMKM di Kota Medan - Rahmi Pamela Putri; Hendra Harmain; Nuri Aslami (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the effect of financial literacy, ease, and usefulness in the decision to use e-money on improving the performance of MSMEs in Medan City. Where researchers want to see how much influence financial literacy has on the decision to use e-money, how much influence ease of use has on the decision to use e-money, how much influence usefulness of use has on the decision to use e-money, how much influence financial literacy, ease, and usefulness in the decision to use e-money on improving the performance of MSMEs in Medan City. The dependent variable is the decision to use e-money, the independent variables are financial literacy, ease of use of e-money, and usefulness of use of e-money. This research method uses a quantitative method. The data used is primary data. Primary data was obtained using a data collection tool in the form of a questionnaire from a sample of 100 MSME actors with the help of the SPSS 25.0 program. The results of the study showed that F Calculation was 35.743> F table (3.090). With a probability value of 0.000 (p <0.05). This means that the variables of Financial Literacy (X1), Ease of Use of E-Money (X2), and Usefulness of Use of E-Money (X3) together have a significant influence on the decision to use e-money to improve the performance of MSMEs in Medan City.